EKSPERIMEN DAN MODEL EKSTRAKSI MINYAK ATSIRI DENGAN BAHAN CYMBOPOGON SP. MENGGUNAKAN HIDROSTEAM DISTILLATION - Zuhdi Ma'sum; Pramono Sasongko (Universitas Tribhuwana Tunggadewi Malang, 2017)
This work has as objective to modeled time extraction and yield of the citronella oil extraction processes from stems by hydrosteam distillation. The process variables evaluated in this study were extraction time, and material weight. The yield is calculated from the relation between mass essential oil obtained and the raw material mass used in the extraction and the quantitative and qualitative analyses of the oils were performed by capillary GC/MS. The experimental condition for the maximum yield, 0.36 %, is the following one: extraction time, 4 h, natural plant. The modeling of these results is proposed from the description of the mass transfer from a single plate particle. Yield curves for all studied conditions were fairly well fitted using one adjustable parameter of the model and the experimental monitoring of oil composition as function of extraction time was realized in laboratory steam distillation apparatus and compared with industrial scale results.